Pelatihan Pembuatan Karikatur 3D Melalui Pemanfaatan Artificial Intelligence (AI) Bagi Guru KB Belia Puraya - Irsal Fauzi; Dewi Ariani; Abdul Aziz; Novita Herawati; Ulfamiyati Ulfamiyati (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The development of Artificial Intelligence (AI) tools in early childhood learning has been a topic of interest in recent years. AI in early childhood education can be used to provide interactive, personalised and adaptive learning experiences. The use of AI tools in early childhood learning has great potential to improve the effectiveness and efficiency of learning. However, it is important to remember that the interaction and support of teachers and parents remains crucial in children's development, and AI should not replace the role of humans in the education process. Artificial intelligence (AI) tools, have been increasingly used in the field of early childhood education (ECE) to enhance learning and development among young children. Previous proof-of-concept studies have shown that AI can effectively improve learning and development in ECD; however, there is a dearth of knowledge on how these studies were conducted and how AI was used throughout these studies. The main problem faced by the partners is the lack of competence of these human resources in managing and applying AI tools in learning, especially in creating 3D caricatures that are useful to attract the attention of students, as well as to promote the school.